PENERAPAN SAK ETAP DALAM LAPORAN KEUANGA N PADA KOPERASI KARYAWAN PT. TATA BUSANA JAKARTA - Dwiyatmoko Pujiwidodo (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2015)
Preparation of financial statements must be based on generally accepted accounting standards. Standards used in the preparation of financial statements is a standard accounting cooperative entities without public Accountability (SAK ETAP). SAK ETAP is the new standard issued bond replaces SFAS No. accountant Indonesia 27. This scientific article is to discuss the implementation of the SAK ETAP Employees Cooperative PT. Tata Busana aimed to find ways of applying SAK ETAP conducted by the Employees Cooperative PT. Tata Busana and conduct a review aspects assessed to see the accuracy of SAK ETAP Employees Cooperative PT. Tata Busana. Based on the results of the research, it was concluded that Based on the results of the research, that the Employees Cooperative PT. Tata Busana has not made full SAK ETAP as standard in the preparation of financial statements. Therefore Cooperative Employees PT. Tata Busana should perform financial statement presentation SAK ETAP with good and complete, in order to provide full information on the financial condition of the Employees Cooperative PT. Tata Busana.                                                                                                                 Keywords : Cooperative, SAK ETAP